European Network to Advance Best Practices and Technology on Medication Adherence: Mission Statement - van Boven, Job FM; Tsiligianni, Ioanna; Potočnjak, Ines; Mihajlović, Jovan; Dima, Alexandra L.; Nabergoj Makovec, Urska; Ágh, Tamás; Kardas, Prezmyslaw; Ghiciuc, Cristina Mihaela; Petrova, Guenka; Bitterman, Noemi; Kamberi, Fatjona; et al. (Frontiers in Pharmacology, 2021)
• Medication non-adherence is associated with almost 200,000 deaths annually and €80-125 billion in the European Union. • Novel technological advances (smart pill bottles, digital inhalers and spacers, electronic pill blisters, e-injection pens, e-Health applications, big data) could help managing non-adherence. • Healthcare professionals seem however inadequately informed about non-adherence, availability of technological solutions in daily practice is limited, and collaborative efforts to push forward their implementation are scarce. • The European Network to Advance Best practices & technoLogy on medication adherencE (ENABLE, COST Action 19132) aims to (1) raise awareness of adherence enhancing solutions, (2) foster knowledge on medication adherence, (3) accelerate clinical application of novel technologies and (4) work collaboratively towards economically viable policy and implementation of adherence enhancing technology across healthcare systems.